Comparison of some properties of four provisional restorations resin: Trim, Tempron, Acropars TRII & Duralay (Aria Dent) - Monzavi A.; Zarati S.; Jafarzadeh T.; Amini MH (Tehran University of Medical Sciences, 2006)
Background and Aim: Use of provisional restorations is one of the important phases in the treatment of patients who need fixed prosthesis. Some physical properties are required for these materials. The purpose of this study was the comparison of some physical properties of 4 kinds of resins: Trim, Tempron, Duralay (Aria Dent) and Acropars TRII. Materials and Methods: In this experimental study, transverse-strength (TS), setting time (ST), polymerization shrinkage (PS) and temperature rise (TR) during polymerization were tested. In transverse strength test, 5 samples of each resin were made. TS testing was done with an Instron testing machine. ST testing (5 samples in each group) was done with Gilmore needle. In PS test, 11 cylindric samples were prepared from each resin and the shrinkage was examined with digital micrometer (up to 24 hours). In TR test, after mixing the powder and liquid of resins (8 samples in each group), the temperature rise was recorded with 10 seconds interval (up to 15 minutes). Data were analyzed with one-way ANOVA and Tukey HSD tests with p<0.05 as the limit of significance. Results: In TS test, all samples of Trim were bent and no fracture was observed, while Tempron and Duralay showed no significant difference. Both Tempron and Duralay revealed high significant difference with Acropars TRII (P <0.01). In ST test, the difference between groups was significant (P<0.01). The lowest ST was observed in Acropars TRII (7 min), and the highest in Tempron (9.53 min). In PS test, significant difference was observed between Trim and Acropars TRII (P<0.01). PS was completed after 120 min in Tempron and Trim groups. However, PS continued to increase in other groups. In TR test, the difference between groups was significant (P<0.05). Duralay showed the highest TR and the lowest was seen in Trim. Conclusion: In this study, Trim showed better properties than other studied groups. Acropars TRII had the lowest strength. The highest temperature rise was recorded for Duralay and Tempron, respectively.